Ischaemia-reperfusion injury in photodynamic therapy-treated mouse tumours - Korbelik, M (Nature Publishing Group, 2003)
Prompted by the observation of ischaemia development during the treatment of tumours by photodynamic therapy (PDT) that is typically followed by a restoration of tumour blood flow and by the indications of secondary superoxide generation after PDT, we aimed in this study to obtain evidence of the induction of ischaemia-reperfusion (I/R) injury in PDT-treated tumours. Using subcutaneous mouse FsaR fibrosarcoma model and Photofrin-based PDT treatment, we have examined the activity of xanthine oxidase (XO, a key enzyme in the I/R injury development) in tumours before and after the therapy. Compared to the levels in nontreated tumours, there was a five-fold increase in the activity of this enzyme in tumours excised immediately after PDT. This burst of elevated XO activity declined rapidly, returning to the pretreatment levels within the next 30 min. Visible reflectance spectroscopy confirmed the occurrence of a PDT-induced strong but temporary reduction in tumour oxygenation. The administration of XO inhibitor oxypurinol prevented this PDT-induced rise in XO activity. The oxypurinol treatment also decreased the extent of neutrophil accumulation in PDT-treated tumours and reduced the level of PDT-mediated cures. These results demonstrate the induction of I/R injury in PDT-treated tumours, and show that it can contribute to the therapy outcome. Since I/R injury is a well-recognised proinflammatory insult, we suggest that its induction in PDT-treated tumours promotes the development of inflammatory response that has become established as a key element of the antitumour effect of PDT.